Built-in microscopes with light guide elements for smartphones and other devices - PANDI ANIRUDDHA BALCHANDRA; MEVADA, JAYSHKUMAR, SEVANTILAL (2023)
The subject matter describes an optical microscope device (3) for a portable imaging system, such as a smartphone. The optical microscope arrangement (3) comprises an optical lens assembly having eight to fifteen lens elements. The optical lens assembly has an optical magnification in the range of about 1 X to about 7.8 X, an Airy radius in the range of about 3 microns to about 23.25 microns, a depth of field in the range of about 20 microns to about 338 microns, a numerical aperture in the range of about 0.015 to about 0.115, a half field of view in the range of about 12 degrees to about 30 degrees, and a length in the range of about 6.5 mm to about 57 mm. 本主题描述了用于便携式成像系统诸如智能电话的光学显微镜装置(3)。光学显微镜装置(3)包括具有八至十五个透镜元件的光学透镜组件。光学透镜组件具有在约1X至约7.8X的范围内的光学放大率、在约3微米至约23.25微米的范围内的艾里半径、在约20微米至约338微米的范围内的景深、在约0.015至约0.115的范围内的数值孔径、在约12度至约30度的范围内的半视场、以及在约6.5毫米(mm)至约57mm的范围内的长度。